Relationship between Initial Management Strategy and Survival in Patients with Gastric Outlet Obstruction due to Gastric Cancer - Blumenthaler, Alisa N. (J Surg Oncol, 2020)
BACKGROUND: The optimal management of gastric outlet obstruction (GOO) due to gastric cancer (GC) is unclear. We examined the relationships between clinical and management variables and outcomes in GC patients with GOO. METHODS: GOO management and clinical course were reviewed in patients with GC and GOO. Cox regression and Kaplan-Meier analyses were used to identify variables predictive of overall survival (OS). RESULTS: The study included 59 patients. Eleven had imaging evidence of metastasis, and 35 had pathologically confirmed peritoneal disease. Initial management included resection in 23 patients, feeding jejunostomy ± decompressive gastrostomy (JT/GT) in 25, surgical gastrojejunostomy in 5, and endoscopic intervention in 6. Seven patients with initial JT/GT underwent resection after neoadjuvant therapy. Median OS(95%CI) was 21.4 (0.0–45.1)months in the up-front resection group (median follow-up, 14.7months) and not reached in those with initial JT/GT, neoadjuvant therapy, and later resection (median follow-up, 26.5months)(P=0.18). On multivariable analysis, clinically positive nodes (hazard ratio[HR]:3.76; 95%CI:1.17–12.12; P=0.03), metastasis on CT (HR:3.97; 95%CI:1.53–10.26;P=0.01) and resection (HR:0.37; 95%CI:0.17–0.79;P=0.01) independently predicted OS. CONCLUSION: In GOO due to GC, OS is similar after treatment with up-front resection compared with JT/GT, neoadjuvant therapy, and later resection. Up-front JT/GT may allow patients to tolerate chemotherapy and improve selection for gastrectomy.